Effects of biomass smoke on pulmonary functions: a case control study - Balcan B; Akan S; Ugurlu AO; Handemir BO; Ceyhan BB; Ozkaya S (International Journal of COPD, 2016)
Baran Balcan,1 Selcuk Akan,2 Aylin Ozsancak Ugurlu,1 Bahar Ozcelik Handemir,3 Berrin Bagcı Ceyhan,4 Sevket Ozkaya5 1Department of Pulmonary Medicine, Baskent University Faculty of Medicine, Istanbul, 2Department of Internal Medicine, Ankara Education and Teaching Hospital, Ankara, 3Department of Pulmonary Medicine, Irmet Hospital, 4Department of Pulmonary Medicine, Marmara University Faculty of Medicine, 5Department of Pulmonary Medicine, Faculty of Medicine, Bahcesehir University, Istanbul, Turkey Background: Biomass smoke is the leading cause of COPD in developing countries such as Turkey. In rural areas of Turkey, females are more exposed to biomass smoke because of traditional lifestyles.Aim: The aim of this study was to determine the adverse effects of biomass smoke on pulmonary functions and define the relationship between duration in years and an index (cumulative exposure index) with altered pulmonary function test results.Participants and methods: A total of 115 females who lived in the village of Kağizman (a borough of Kars located in the eastern part of Turkey) and were exposed to biomass smoke were included in the study. The control group was generated with 73 individuals living in the same area who were never exposed to biomass smoke.Results: Twenty-seven (23.8%) females in the study group and four (5.5%) in the control group had small airway disease (P=0.038). Twenty-two (19.1%) females in the study group and ten (13.7%) in the control group had obstruction (P=0.223). Twenty (17.3%) females in the study group who were exposed to biomass smoke had restriction compared with ten (13%) in the control group (P=0.189). The duration needed for the existence of small airway disease was 16 years, for obstructive airway disease was 17 years, and for restrictive airway disease was 17 years. The intensity of biomass smoke was defined in terms of cumulative exposure index; it was calculated by multiplying hours per day, weeks per month, and total years of smoke exposure and dividing the result by three.Conclusion: Exposure to biomass smoke is a serious public health problem, especially in rural areas of developing countries, because of its negative effects on pulmonary functions. As the duration and the intensity of exposure increase, the probability of having altered pulmonary function test results is higher. Keywords: biomass, exposure, pulmonary function, duration, intensity